PENGEMBANGAN BUKU PENGAYAAN PENGETAHUAN KAJIAN FISIKA DALAM ALAT MUSIK KORDOFON UNTUK PEMBELAJARAN BERMAKNA - Hani Kurniawati; Desnita Desnita; Siswoyo Siswoyo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The purpose of this research was to develop a physics enrichment book based on the four identified principled which include content, presentation, language, and graphics. The research method used in this development is Research and Development which refer to the five-stages ADDIE model. This development result in an enrichment book that presents the concept of music and musical instruments explained by physics phenomena which includes sound waves, resonance, wavelength, frequency, sound intensity, timbre, and music scales. The enrichment books that is developed is then validated by expert and tested to indicate whether the book is effective or not, thus, creating a meaningful learning for students. The result of the media expert validation is 94%, education expert validation is 81%, content expert validation is 98% and originality validation is 89%. The result showed in the field-test of the product was at highly appropriate level with an average score of 86% from the teachers and 85% from the students. The books’ meaningful learning was tested to education expert, teachers, and students, resulting in an average score of 79% from the education expert, 81% from the teachers, and 85% from the students. Hence, based on the validation and field-test data, it can be conclude that the enrinchment book that has been develop is the worth to be used as a source of meaningful learning for students. Keywords: Meaningful Learning, Enrichment Books, Chordophone Musical Instrument, Sound Waves.